Odpowiedź:
a) (1 [tex]\frac{2}{3}[/tex]*3-[tex]1,5^{2}[/tex]:4,5):2= ([tex]\frac{5}{3}[/tex]*3 -2,25:4,5):2=(5-0,5):2= 4,5:2=2,25
b) [tex]\frac{(1,5+\frac{2}{3}):2\frac{1}{6} }{\frac{3}{4}-0,5 }[/tex]= [tex]\frac{(\frac{3}{2}+\frac{2}{3})*\frac{6}{13} }{0,25}= \frac{\frac{9}{6}+\frac{4}{6} }{0,25}= \frac{1}{0,25}=4[/tex]
c)[tex]\frac{\frac{2}{3}+\frac{1}{6} }{\frac{31}{30} }=\frac{\frac{4}{6} +\frac{1}{6} }{\frac{31}{30} } =\frac{\frac{5}{6} }{\frac{31}{30} }=\frac{5}{6}*\frac{30}{31} = \frac{25}{31}[/tex]
d) [tex]\frac{0,6}{(2,5-1\frac{2}3)*\frac{1}{6} } =\frac{\frac{3}{5} } {(\frac{5}{2}-\frac{5}{3})*\frac{1}{6} } =\frac{\frac{3}{5} }{\frac{5}{36} }= \frac{3}{5} *\frac{36}{5}=\frac{108}{25}=4 \frac{8}{25} }[/tex]